Sale and Purchase of Chicken with an Opera Note System in the Perspective of Sharia Economic Law - Khotamin , Nur Alfi; Suryani, Wulan Indah; Abroza, Ahmad (Journal Tafkirul Iqtishodiyyah, 2021)
As time goes by with the developments that occur, humans in order to meet the needs of daily life, buying and selling problems are increasing and the implementation is different. As well as buying and selling done by breeders / sellers of chicken pieces in Metro City. The buying and selling carried out by them sometimes uses the operating note system. This system is also often carried out by chicken sellers in markets, especially the Tejo Agung People's Market. The practice of buying and selling chicken pieces at the Tejo Agung People's Market with an oper-note system is carried out by collectors selling chicken pieces to chicken traders in the market without re-weighing the chickens that have been taken from the center/coop. The research approach used in this study is a qualitative approach. The results obtained from this study are expected to provide a comprehensive and systematic picture which is then analyzed so that general conclusions can be drawn. This writing is based on the results of interviews with chicken collectors and sellers at the Tejo Agung People's Market. Based on the results of the research and discussion above, it can be concluded that in the practice of buying and selling chicken pieces that occurred at the Tejo Agung People's Market is to use an oper note system, namely if the seller of chicken pieces sells the chicken to consumers, they do not weigh the weight of the chickens anymore. because of the risks involved. however, the seller of the slaughtered chicken takes advantage of the lower price to his consumers. The practice of buying and selling chicken pieces with a note-taking system can harm one party. The losses experienced by consumers are quite significant and the buying and selling contains an element of uncertainty or gharar, and this kind of buying and selling is buying and selling which is prohibited by Islam. The sale and purchase of chicken pieces with a note-taking system is not in accordance with sharia economic law